Comparison of Rps loci toward isolates, singly and combined inocula, of Phytophthora sojae in soybean PI 407985, PI 408029, PI 408097, and PI424477 - Clevinger, Elizabeth M.; Biyashev, Ruslan; Schmidt, Clarice; Song, Qijian; Batnini, Amine; Bolaños-Carriel, Carlos; Robertson, Alison E.; Dorrance, Anne E.; Saghai Maroof, M. A. (Frontiers in Plant Science, 2024)
For soybean, novel single dominant Resistance to Phytophthora sojae (Rps) genes are sought to manage Phytophthora root and stem rot. In this study, resistance to P. sojae was mapped individually in four recombinant inbred line (RIL) populations derived from crosses of the susceptible cultivar Williams with PI 407985, PI 408029, PI 408097 and PI424477, previously identified as putative novel sources of disease resistance. Each population was screened for resistance with 5 to 7 isolates of P. sojae separately over multiple F7-F10 generations. Additionally, three of the populations were screened with inoculum from the combination of 3 P. sojae isolates (PPR) which comprised virulence to 14 Rps genes. Over 2,300 single-nucleotide polymorphism markers were used to construct genetic maps in each population to identify chromosomal regions associated with resistance to P. sojae. Resistance segregated as 1 or 2 genes to the isolates and 1 gene towards PPR in each population and mapped to chromosomes 3, 13, or 18 in one or more of the four RIL populations. Resistance to five isolates mapped to the same chromosome 3 region: OH7 (PI 424477 and PI408029), OH12168, OH7/8, PPR (PI 407985) and 1.S.1.1 (PI408029). The resistance regions on chromosome 13 also overlapped for OH1, OH25, OH-MIA (PI424477), PPR (PI 424477, PI 407985, and PI 408097), PPR and OH0217 (PI 408097) and OH4 (PI 408029), but were distinct for each population suggesting multiple genes confer resistance. Two regions were identified on chromosome 18 but all appear to map to known loci, notably resistance to the combined inoculum (PPR) did not map at this locus. However, there are putative new alleles in 3 of 4 populations, 3 on chromosome 3 and 2 on chromosome 13 based on mapping location but also known virulence in the isolate used. This characterization of all the Rps genes segregating in these populations to these isolates will be informative for breeding but the combined inoculum was able to map novel loci. Furthermore, within each of these P. sojae isolates there was virulence to more than the described Rps genes and the effectiveness of the novel genes requires testing to larger populations.